ISLAMIC ARBITRATION IN INDONESIA - Dr. Muhammad Arifin S.H., M.Hum (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Indonesia law recognizes the islamic arbitratino which is so called Sharia Arbitration.